T. Swann Harding papers - Harding, T. Swann (Thomas Swann), 1890-
Chiefly letters from editors and publishers concerning publication of Harding's books and articles on literary and scientific matters. Includes a typescript of his unpublished work entitled, "110 Years of Federal Aid to Agriculture." Correspondents include Frederick Lewis Allen, Walter C. Alvarez, Thurman Wesley Arnold, Hugo LaFayette Black, Richard Wilson Boynton, V. F. Calverton, C. D. Darlington, Elmer Holmes Davis, Durant Drake, Milton Stover Eisenhower, Henry Pratt Fairchild, H. M. Foster, Ossip Gabrilowitsch, Frederick S. Hammett, Waldemar Kaempffert, Lincoln MacVeagh, H. L. Mencken, Francis L. Pollack, Vilhjalmur Stefansson, Tiffany Thayer, and C. H. Ward.
Author, editor, and civil servant.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Allen, Frederick Lewis, -- 1890-1954 -- Correspondence; Alvarez, Walter C. -- 1884-1978 -- Correspondence; Arnold, Thurman Wesley, -- 1891-1969 -- Correspondence; Black, Hugo LaFayette, -- 1886-1971 -- Correspondence; Boynton, Richard Wilson, -- 1870- -- Correspondence; Calverton, V. F. -- 1900-1940 -- Correspondence; Darlington, C. D. -- 1903- -- Correspondence; Davis, Elmer Holmes, -- 1890-1958 -- Correspondence; Drake, Durant, -- 1878-1933 -- Correspondence; Eisenhower, Milton Stover, -- 1899-1985 -- Correspondence; Fairchild, Henry Pratt, -- 1880-1956 -- Correspondence; Foster, H. M. -- Correspondence; Gabrilowitsch, Ossip, -- 1878-1936 -- Correspondence; Hammett, Frederick S. -- 1885- -- Correspondence; Kaempffert, Waldemar, 1877-1956 -- Correspondence; MacVeagh, Lincoln, -- 1890-1972 -- Correspondence; Mencken, H. L. -- 1880-1956 -- Correspondence; Pollack, Francis L. -- Correspondence; Stefansson, Vilhjalmur, -- 1879-1962 -- Correspondence; Thayer, Tiffany, -- 1902-1959 -- Correspondence; Ward, C. H. -- 1872-1935 -- Correspondence; United States. -- Department of Agriculture; Agriculture; Economic assistance, Domestic; Publishers and publishing; Authors; Civil servants; Editors